The use of Brain Gym Improves Emotional Intelligence Ability of Elementary School Students - Yuliana Risa; Tri Sakti Widyaningsih (GLOBAL HEALTH SCIENCE GROUP, 2022)
Emotional intelligence is a human ability to evaluate, manage, and control self-emotion or around people. The effort to improve children's emotional intelligence is not only through playing but giving practice techniques such as brain gym. Brain gym is a simple motion-based system that is fun, improves learning ability, processing of complete affection information, and fun. So, it can improve children's emotional intelligence. Purpose to know the use of brain gym improves emotional intelligence ability of elementary school students in Jragung Vilage Karangawen Sub-District Demak Regency. The case study used descriptive statistic technique. The instrument is brain gym observation sheet, pre-test and post-test of emotional intelligence questionnaire with X criteria ≥ 48: High, X ≥ 24: Low. The case study used 4 subjects and data presentation in narrative and table. The subject on third day, the average emotional intelligence of children before brain gym practice is 51, it is categorized as low and 53 is the highest. After giving Brain Gym practice, the highest value is 67, the lowest is 58. The result of the case study on the use of brain gym to improve the emotional intelligence ability of elementary school students in Jragung Village Karangawen Sub-District Demak regency is effective. It is for improvement in teaching and understanding theory about the basic concept of child care, about factors that influence emotional intelligence of children level, especially using brain gym. It is effective to improve the emotional intelligence of elementary school students.